HUBUNGAN KARAKTERISTIK IBU DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN - Rahayu, Esti (Akbid Wirabuana, 2022)
Background: The number of stunting under-five cases in the world has decreased every year. However, WHO projects that by 2025 the number of stunted children under five will not reach the World Health Assembly's 2025 target, which is to reduce the number of stunting to 100 million. The World Health Organization (WHO) limits the stunting problem that occurs in every country, province, and district by 20%. In addition, the Indonesian president is targeting a reduction in the stunting rate to 14% in 2024. However, Indonesia is still at 30.8% in 2018 even though it has decreased compared to 2013 which was 37.2%. It can be seen that the number of stunting children in Indonesia is still far from the target, so special attention is needed to make Indonesia more advanced in the future. Objective: To determine the factors related to the incidence of stunting in toddlers aged 24-59 months in the Sukaraja Nuban Health Center Working Area in 2021. Methods: This study was an analytical observational study with a case-control design. The population in this study were toddlers aged 24-59 months. The sampling technique was simple random sampling and obtained a sample of 60 cases and 60 controls. Results: variables related to stunting were nutritional status (ρ=0.003, OR=0.280), maternal height (ρ=0.031, OR=2.626) and mother's education (ρ=0.019, OR= 2.833). Conclusion: There is a relationship between maternal nutritional status, maternal height and maternal education, with the incidence of stunting.Keywords : Stunting, Oddlers, Mother’s characteristics